The Experience of Using of Dexmedetomidine for Sedation in Cardiac Intensive Care Units - O. N. Lisichkina; S. M. Boyko; Ya. P. Truba; V. V. Lazoryshynets (Ukrainian Journal of Cardiovascular Surgery, 2017)
The article presents the experience of using of dexmedetomidine for sedation in cardiac intensive care units. Comparative analysis of using of dexmedetomidine and propofol in children after surgical treatment of congenital heart disease is conducted.